Immediate Versus Delayed Surgical Treatment of Lumbar Disc Herniation for Acute Motor Deficits: The Impact of Surgical Timing on Functional Outcome. Issue 7 (1st April 2019) - Petr, Ondra; Glodny, Bernhard; Brawanski, Konstantin; Kerschbaumer, Johannes; Freyschlag, Christian; Pinggera, Daniel; Rehwald, Rafael; Hartmann, Sebastian; Ortler, Martin; Thomé, Claudius
Abstract : Study Design: A retrospective cohort study. Objective: The aim of the study was to assess the impact of time to surgery in patients with motor deficits (MDs) on their functional outcome. The current single-center study presents results of emergency surgery for LDH in a group of patients with acute paresis in a "real-world" setting. Summary of Background Data: MDs are a frequent symptom of lumbar disc herniation (LDH). Although surgery within 48 hours has been recommended for cauda-equina syndrome, the best timing of surgery for acute MDs continues to be debated. The effect of early surgery has been proposed but remains to be unproven. Methods: A total of 330 patients with acute paresis caused by LDH acutely referred to our department and surgically treated using microsurgical discectomy from January 2013 to December 2015 were included. Based on the duration of MD and surgical timing, all patients were classified into two categories: Group I included all patients with paresis <48 hours and Group II included all patients with paresis >48 hours. Patient demographics, LDH/clinical/treatment characteristics, and outcomes were collected prospectively. Severity of paresis [Medical Research Council (MRC) Grade 0–4], surgery-related complications, functional recovery of motor/sensory deficits, sciatica, retreatment/recurrence rates, and overall neurological outcome were analyzed. Results: Group I showed significantly faster recovery of moderate/severe paresis (MRC 0–3) at discharge, and 6-weeks/3-months follow up ( P ⩽ 0.001), whereas there were no significant differences in recovery for mild paresis (MRC 4). Sensory deficits also recovered substantially faster in Group I at 6-weeks ( P  = 0.003) and 3-months follow up ( P  = 0.045). Body mass index, preoperative MRC-grade, and duration of MDs were identified as significant predictors for recovery of paresis at all follow ups with substantial impact on patient reported outcomes including sciatica and/or dermatomal sensory deficits. Conclusion: Given the superior rates of neurological recovery of acute moderate/severe MDs, immediate surgery should be the primary option. However, a prospective randomized clinical trial is needed to confirm the superiority of emergency surgery. Level of Evidence: 3 Abstract : The effect of early surgery for acute paresis due to LDH has been proposed but remains to be unproven thus impending the development of guidelines particularly for on-call decisions.The current single-center study presents results of emergency surgery for LDH in an unselected group of patients with acute paresis.